Tecnologia e comunicação nas instituições de ensino superior : o uso do SACI na UFSCar - Vieira, Adriane Aparecida Vasconcelos (2015)
This dissertation is a result from a bibliographic, documentary, descriptive, qualitative research, in the subject about the using of the technological tools of information at the communication in the institutions of college education. The central porpuse of the research is investigate how the Support of Sistem for an Integrated Communication (SACI in portuguese) is used at the University of São Carlos (UFSCar). This dissertation makes the assumption that SACI can serve the necessities of the most different kinds of communication inside a Federal University. Concepts as public communication, organizacional, institutional, integrated, technology and democratize of knowledge are presented. The study presents an analysis that makes a concern of many kinds of communicatiom with SACI, showing how this software handle with the communication features. Furthermore, this work brings a broad view of how the SACI is instaled and is being used in UFSCar s site. To complement this study, was made a descriptive qualitative research with Prof. PhD. Rodrigo Francisco and Master Mariana Pezzo. The methodological procedure used a crossbred treatment, using questions forms analysed with documents and books. After the data and information survey, it was established that SACI has uncountable functions that resulted in many positive amendments to management of the information of UFSCar, and for being an instrument that can be adapted according to the most different organizational needs, is indispensable to estimate the implatation of the system in others intitutions, as an example, the Federal University of Uberlândia (UFU), aim at improvement of the communication management in these oganizations.